Keputusan Pembelian Ditinjau Dari Gaya Hidup Dan Kualitas Produk (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Wijaya Kusuma Surabaya Yang Membeli Helm CARGLOSS) - Zeva Aurellia Lasubu; Wiwik Herawati (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2023)
The problems studied were lifestyle and product quality in influencing the decision to purchase CARGLOSS helmets among students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. So the goal to be achieved is to find out lifestyle and product quality in influencing the decision to buy a CARGLOSS helmet for FEB UWKS students. FEB UWKS students as the population. The sample based on purposive sampling is 80 respondents. Data was collected by distributing questionnaires. The analysis uses multiple linear regression and the hypothesis is tested by t test. As a result, lifestyle and product quality have a partially significant effect on the decision to purchase CARGLOSS helmets among FEB UWKS students. The contribution of lifestyle and product quality in influencing the decision to purchase CARGLOSS helmets for FEB UWKS students is 41.6%.